1994
DOI: 10.1113/jphysiol.1994.sp020378
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of a novel type of GABA response in rat CA3 hippocampal neurones during development.

Abstract: 1. Intracellular recordings were used to study the effects of gamma‐aminobutyric acid (GABA) on rat CA3 hippocampal neurones during the first two weeks of postnatal life. 2. In the presence of tetrodotoxin (TTX, 1 microM), from postnatal day 0 (P0) to P12 both associated with an increase in input conductance whereas baclofen (30‐100 microM) produced a membrane hyperpolarization. 3. Bicuculline (50 microM) reduced the effects of GABA and abolished the response to isoguvacine without affecting the response to ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
4
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 31 publications
2
59
4
1
Order By: Relevance
“…However, these responses were highly unusual because they were blocked by low concentrations of bicuculline (10 M) as well as the GABA C receptor antagonist TPMPA. This contrasts strikingly with previous studies in which responses to CACA at concentrations of up to 1 mM were resistant to very high concentrations of bicuculline (up to 100 M) and were therefore regarded as mediated by GABA C (comprising only subunits) and not GABA A receptors (Strata and Cherubini, 1994;Akasu et al, 1999). Because the CACA responses we observed were reliant on the 1 subunit, but were not caused by activation of a receptor comprising only subunits, as indicated by bicuculline sensitivity, we tested the hypothesis that the 1 subunit was present in a receptor that also contained GABA A subunits.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, these responses were highly unusual because they were blocked by low concentrations of bicuculline (10 M) as well as the GABA C receptor antagonist TPMPA. This contrasts strikingly with previous studies in which responses to CACA at concentrations of up to 1 mM were resistant to very high concentrations of bicuculline (up to 100 M) and were therefore regarded as mediated by GABA C (comprising only subunits) and not GABA A receptors (Strata and Cherubini, 1994;Akasu et al, 1999). Because the CACA responses we observed were reliant on the 1 subunit, but were not caused by activation of a receptor comprising only subunits, as indicated by bicuculline sensitivity, we tested the hypothesis that the 1 subunit was present in a receptor that also contained GABA A subunits.…”
Section: Discussioncontrasting
confidence: 54%
“…3A). This was unexpected because, in immature hippocampal (Strata and Cherubini, 1994) and pelvic ganglion (Akasu et al, 1999) neurons, CACA at concentrations of up to 1 mM could elicit responses that were resistant to very high bicuculline concentrations (100 M) and were mediated by GABA C receptors. Nevertheless, we observed a similar profile of responses with low concentrations of GABA (5-20 M; n ϭ 4) and muscimol (0.5-2 M; n ϭ 5) (Fig.…”
Section: Atypical Gaba Receptor Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have suggested the presence of a bicuculline-resistant GABA C -like receptor in the hippocampus during the first 2 weeks of postnatal development (Strata and Cherubini, 1994) and 2 subunit mRNA has been detected in postnatal day 5 and adult rat hippocampus by Northern blot and reverse transcription-PCR analyses (Boue-Grabot et al, 1998), we observed no evidence of GABA-evoked current mediated by endogenous GABA C receptors in control neurons. In contrast to previous reports of no desensitization of 1 subunits expressed in Xenopus oocytes (Cutting et al, 1991), our 1 -GFP-neurons exhibited slow but significant desensitization during GABA application.…”
Section: Discussioncontrasting
confidence: 48%
“…Remarkably, GABA C receptors are insensitive to the GABA A competitive antagonist bicuculline (Sivilotti and Nistri 1991) and appear to be exclusively composed of q subunits (q 1 , q 2 , and q 3 ) that yield homomeric and heteromeric receptors (Zhang et al 2001). GABA C receptors are highly expressed in the retina and other visual areas, but q subunits were found to be widely distributed in the CNS (Strata and Cherubini 1994;Enz et al 1995;Albrecht et al 1997;Boue-Grabot et al 1998;Wegelius et al 1998;Enz and Cutting 1999) and their expression is developmentally regulated (Ogurusu et al 1999;Didelon et al 2002;Rozzo et al 2002;Liu et al 2004;Alakuijala et al 2005). Functional GABA C receptors were localized at many different neuronal subtypes (Feigenspan et al 1993;Strata and Cherubini 1994;Martina et al 1997;Pasternack et al 1999;Alakuijala et al 2006).…”
mentioning
confidence: 99%